the Investigating the Implementation of Process Approach to the Teaching and Learning of Writing Skills: The Case of Madda Walabu University - Yitayal damtew zeleke (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2022)
The main objective of this research was to investigate the perceptions of Madda Walabu University writing skills teachers and students about writing skills. To achieve this, a descriptive research design through quantitative questionnaires for students and qualitative semi-structured interview for the teachers was employed. While quantitative data were analyzed using a descriptive SPSS analysis, qualitative data were analyzed using a thematic analysis. The population for this study were 1st year 5 male and 15 female and 2nd year 5 male and 8 female totally 33 undergraduate English as a foreign language students and their 2 writing instructors. This was because 1st year undergraduate English as foreign language students take the writing course i.e. Basic Writing Skills and 2nd year undergraduate English as a foreign language students take the writing course i.e. Advanced Writing Skills. First, a questionnaire was distributed to elicit student’s perceptions and then the 2 teachers were interviewed. The overall results demonstrated that although, the instructor’s perceptions about themselves as writing skills course instructor was high, the teaching of writing skills in Madda Walabu University undergraduate English language and literature department was found to be insufficient and thus hampered the enhancement of the students writing ability. The findings of the study also revealed that majority of the students have positive perception about the importance of learning writing skills. Finally, recommendations were forwarded based on the conclusions so as to promote the teachers and students perceptions and maximize the practice of teaching and learning writing at university level.